Constructing knowledge: an experience of active and collaborative learning in an ICT classroom - Simões, Dora (2012)
This paper reports on the impact of the implementation of active and collaborative practices in ICT (information and communication technologies) classrooms. Both of these approaches convey a lot of responsibility from the teacher to the students and the hoping, as backed up by the literature, is to promote deeper learning and reasoning skills at a higher level. The question is: how do you do all that? This research describes a specific environment that makes use of collaborative tools, like wikis and forums within an e-learning platform and of specific CRM (customer relationship management) software. In order to analyze how this learning environment gets learners actively involved in learning and working together in productive ways, students were surveyed by responding to questionnaires. Several cause-effect relations underlying the teaching-learning methodology and the students’ performance are discussed.